Exchange rate targeting versus inflation targeting: Empirical analysis of the impact on employment and economic growth - Borivoje Krušković (Journal of Central Banking Theory and Practice, 2020)
This paper analyses the effects of two alternative monetary strategies (exchange rate targeting and inflation targeting) on economic growth and employment. On the panel of 18 countries for the period from 1996 to 2013, I tested the hypothesis that countries in exchange rate targeting have a higher rate of GDP growth and lower inflation rate. In order to test the impact of exchange rate policy on economic growth and prices, I applied dynamic panel two stepwise method of least squares (2SLS method) and they were evaluated by two independent regression equation. In order to allow the comparison of results related to exchange rate targeting, the effects of the introduction of inflation targeting in the unemployment rate were also estimated using the panel method two stepwise least squares (2SLS method). Results of empirical studies show that countries with inflation targeting have a lower rate of economic growth and higher unemployment.
Keywords: E31; E42; E52; E58; F31; 330; exchange rate targeting; inflation targeting; monetary strategy; economic growth; employment